Bioluminescence Imaging in Mouse Models Quantifies β Cell Mass in the Pancreas and After Islet Transplantation - Virostko, John (2009)
PURPOSE: We developed a mouse model that enables non-invasive assessment of changes in β cell mass. PROCEDURES: We generated a transgenic mouse expressing luciferase under control of the mouse insulin I promoter [mouse insulin promoter-luciferase-Vanderbilt University (MIP-Luc-VU)] and characterized this model in mice with increased or decreased β cell mass and after islet transplantation. RESULTS: Streptozotocin-induced, diabetic MIP-Luc-VU mice had a progressive decline in bioluminescence that correlated with a decrease in β cell mass. MIP-Luc-VU animals fed a high-fat diet displayed a progressive increase in bioluminescence that reflected an increase in β cell mass. MIP-Luc-VU islets transplanted beneath the renal capsule or into the liver emitted bioluminescence proportional to the number of islets transplanted and could be imaged for more than a year. CONCLUSIONS: Bioluminescence in the MIP-Luc-VU mouse model is proportional to β cell mass in the setting of increased and decreased β cell mass and after transplantation.